Expanding the conversation: Family-School Collaboration - Sawatzky, Donald; Paré, David (Canadian Journal of Counselling and Psychotherapy, 2007)
The two powerful systems of the family and the school are too often isolated from each other when it comes to the welfare of the child experiencing difficulties. This paper proposes a means of closing that gap—a process whereby school counsellors can facilitate family-school meetings. The authors propose that not only are family school meetings a viable option in a constraining economic context, but they promise more enduring changes around declared problems because they facilitate the sharing of meanings among various levels of systems in the child's life. While this collaborative approach attends to systemic concerns, it shies away from directive interventions, favouring a view of counselling as therapeutic conversation where meanings are co-constructed among participants.